1996
DOI: 10.1023/a:1016066325476
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The increased free energy differences for the binding of the enantiomers of both drugs to HSA in the presence of octanoic acid is closer to the value deemed to be necessary for the separation of enantiomers by Davenkov, and shows the importance of the addition of octanoic acid to the mobile phase in the separation of these enantiomers on immobilized albumin columns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…7,58 This triad of residues is highly conserved in mammalian albumins, 59 indicating the importance of intermolecular interactions at this location. However, for FA4 the carboxylate head-groups of fatty acids are hydrogen-bonded to Arg410, Tyr411, and Ser489, which are the most important residues for IBU binding as well.…”
Section: Fa3/fa4 Binding Sitementioning
confidence: 99%
See 1 more Smart Citation
“…7,58 This triad of residues is highly conserved in mammalian albumins, 59 indicating the importance of intermolecular interactions at this location. However, for FA4 the carboxylate head-groups of fatty acids are hydrogen-bonded to Arg410, Tyr411, and Ser489, which are the most important residues for IBU binding as well.…”
Section: Fa3/fa4 Binding Sitementioning
confidence: 99%
“…Plasmatic fatty acids probably modulate competitively and allosterically IBU binding to HSA, which could explain the experimental dissociation equilibrium constant value of 10 À6 M for the IBU-HSA interaction system. 7,58 This triad of residues is highly conserved in mammalian albumins, 59 indicating the importance of intermolecular interactions at this location.…”
Section: Fa3/fa4 Binding Sitementioning
confidence: 99%
“…Several studies have suggested that R-and S-ibuprofen have one common binding site on the HSA [35,44,75]. In addition, S-ibuprofen had at least one other major binding region [35,44,75]. The association equilibrium constant for R-ibuprofen with HSA has been estimated to be 5.3 × 10 5 M −1 at pH 6.9 and 25°C.…”
Section: Chiral Separation Of Racemic Ibuprofenmentioning
confidence: 99%
“…In this article, we propose a chemical model for determining the mutual and specific lowaffinity binding sites. We use HSA as a model protein because it is a major drug carrier protein in blood and has large binding capacity for most drugs and endogenous metabolites [26][27][28][29][30][31]. Two non-steroidal anti-inflammatory drugs, tolmetin (TOL) and salicylic acid (SAL), were used as ligands.…”
Section: Introductionmentioning
confidence: 99%